Experimental study of environmental factors' impact on surface leakage currents of high-voltage support insulators - Kotysh, A. I.; Petrova, K. H.; Pavlenko, V. M.; Volianyk, O. Y. (Energy and Automation, 2025)
Ensuring the reliability of high-voltage insulation systems is critical for the safe and efficient operation of power equipment. Surface leakage currents, formed under the influence of atmospheric and anthropogenic factors, accelerate the aging of insulation materials, reduce their dielectric strength, and increase the risk of emergency failures. Particular attention is given to the combined impact of relative humidity, temperature fluctuations, surface contamination, and wind speed, which together create highly unfavorable conditions for the operation of insulation systems and necessitate the implementation of automated approaches to monitoring and managing their condition.The aim of this work is to experimentally determine the influence of key climatic and anthropogenic factors on the leakage currents of support insulators, to assess the relative contribution of these factors, and to construct generalized graphical dependencies. The results obtained can be used to predict the performance of insulation systems and to develop automated methods for optimizing the operating modes of power equipment.The research was conducted on IOS-35-1000 UHL insulators operated at substations in the central region of Ukraine.It was found that the dominant influencing factors are relative humidity (30%), negative temperature difference (25%), and surface contamination (20%). Absolute humidity, duration of moisture exposure, and wind speed have a secondary effect on leakage current, with wind partially reducing surface conductivity. The experimental graphical dependencies reflect the dynamics of conductive layer formation under various moistening conditions.Critical operating conditions for insulation systems arise when high humidity, negative temperature differences, and the presence of a hygroscopic contamination layer are combined. The results obtained can be used to predict the reliability of insulation structures and to improve automated insulation condition monitoring systems.Key words: high-voltage insulator, leakage current, surface contamination, atmospheric factor, experimental study.